Identidades, práticas e moralidades transnacionais: etnografia da esgrima japonesa no Brasil - Lourenção, Gil Vicente Nagai (2009)
The focus of my recearch was the negotiation of 'identity' for Japanese, Japanese descendants, and people without Japanese ancestry living in Brazil with a vehicle a sport called Kendo [Japanese fencing]. In this martial practice noticed a disciplining of the body and attitudes that consciously and unconsciously defines negotiations of 'identity and difference' established social relationships activated by practitioners. The research problem was located as the negotiation process of 'Japanese identity' and its moral postulate in Brazil with regard to this martial practice. And as she and all ethical and moral training in due to contact with immigrant teachers provide support for such a Japanese ontology. The hypothesis that I favor is the hallmark of an unconscious system of value that allows the classification in terms of proximity and distance in relation to a particular notion of Japaneseness. In short, there are characters to biological properties which make the ratings, but the closer it is knowledge of the Japanese. Kendo, taken as an unit of analysis is a machine, a device of Japaneseness - that is, a mechanism for the production of 'Japanese' myth and rith speeches, re-designed and updated from an objective and subjective body-size.